(untitled) (International Journal of Geoscience, Engineering and Technology, 2025)
Forest fires, intensified by anthropogenic pressure and climate change, pose a significant threat to ecosystems and socioeconomic activities. This study aimed to perform wildfire risk zoning in Teófilo Otoni, Minas Gerais, in order to identify vulnerable areas and support conservation and sustainable management policies. Maps were developed using QGIS software, considering slope aspect, gradient, distance from urban clusters, proximity to road networks, and land use and land cover, based on data from the Digital Elevation Model (MDE), the Spatial Data Infrastructure of the State Environmental System (IDE-SISEMA) and the MapBiomas Project, Collection 10 (2024). The results showed that 65.60% of the municipal territory presents Moderate to Very High risk, particularly in agricultural areas, north-facing slopes, and regions near highways. The consistency of the zoning was confirmed by the 227 fire hotspots recorded between 2020 and 2025, highlighting its relevance for local environmental planning.